THE EFFECT OF PBL INTEGRATED WITH IGYA SER HANJOB'S LOCAL WISDOM TO IMPROVE STUDENTS' PROBLEM SOLVING SKILLS IN CONSERVATION BIOLOGY COURSES - Iwan Iwan; Sutiman Bambang Sumitro; Ibrohim Ibrohim; Fatchur Rohman (Universitas Labuhanbatu, 2024)
This research aims to determine the effect of PBL integrated with Igya Ser Hanjob's local wisdom on students' problem solving skills in the Conservation Biology course. The sample for this research was Biology Education Semester VII students taking Conservation Biology courses, totaling 48 students, namely class A (experimental class) with 24 students and class B (control class) with 24 students. This type of research is quasi-experimental research using a nonequivalent control group design. The instruments used in this research were description tests and questionnaires. The data obtained were analyzed using descriptive and inferential statistics which had previously met the requirements for normality and homogeneity, then the Anacova test was carried out using the SPSS IMB 20 program. The results of the research showed 1) there was an increase in the average score of students' problem solving skills after implementing PBL containing local wisdom 2 ) there is a difference in student problem solving skills between the group of students who took part in PBL containing Igya ser hanjob local wisdom and the group of students who took part in conventional learning as evidenced by a significance value of 0.000 < 0.05. Therefore, it can be concluded that PBL learning integrated with Igya Ser Hanjob's local wisdom can improve students' problem solving skills.Keywords: PBL, Problem solving skills, Igya ser hanjop, Local wisdom, Biology Conservation